Physical Training vs. Perindopril Treatment on Arterial Stiffening of Spontaneously Hypertensive Rats: A Proteomic Analysis and Possible Mechanisms - Miotto, Danyelle Siqueira [UNESP]; Duchatsch, Francine [UNESP]; Dionizio, Aline; Buzalaf, Marília Afonso Rabelo; Amaral, Sandra Lia [UNESP] (MDPI, 2023)
(1) Background: Arterial stiffness is an important predictor of cardiovascular events. Perindopril and physical exercise are important in controlling hypertension and arterial stiffness, but the mechanisms are unclear. (2) Methods: Thirty-two spontaneously hypertensive rats (SHR) were evaluated for eight weeks: SHRC (sedentary); SHRP (sedentary treated with perindopril—3 mg/kg) and SHRT (trained). Pulse wave velocity (PWV) analysis was performed, and the aorta was collected for proteomic analysis. (3) Results: Both treatments determined a similar reduction in PWV (−33% for SHRP and −23% for SHRT) vs. SHRC, as well as in BP. Among the altered proteins, the proteomic analysis identified an upregulation of the EH domain-containing 2 (EHD2) protein in the SHRP group, required for nitric oxide-dependent vessel relaxation. The SHRT group showed downregulation of collagen-1 (COL1). Accordingly, SHRP showed an increase (+69%) in the e-NOS protein level and SHRT showed a lower COL1 protein level (−46%) compared with SHRC. (4) Conclusions: Both perindopril and aerobic training reduced arterial stiffness in SHR; however, the results suggest that the mechanisms can be distinct. While treatment with perindopril increased EHD2, a protein involved in vessel relaxation, aerobic training decreased COL1 protein level, an important protein of the extracellular matrix (ECM) that normally enhances vessel rigidity.
Keywords: collagen and aerobic training; perindopril; pulse wave velocity; SHR